1989
DOI: 10.1111/j.1600-0714.1989.tb01573.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral hairy leukoplakia: observations in 95 cases and review of the literature

Abstract: Oral hairy leukoplakia; observations in 95 cases and review of the literature, J Oral Pathol Med 1989; 18; 410-415. Oral hairy leukoplakia (HL) was observed in 25.4% of 373 HIV-seropositive patients (« = 95). 87 were men of an average age of 37.1 yr, 8 were women (30,3 yr). 71.6% of the patients were male homosexuals. At initial diagnosis of HL the majority of cases was elassified as CDC IVc, (45,3%) and CDC II (22,1%), Average CD4/CD8 ratio {n = 19) was 0,24 with a range of 0,04-1,0, Thirty biopsies of HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
14
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 29 publications
5
14
0
1
Order By: Relevance
“…The most common histopathological features observed in our study were similar to those found in other studies [20,27,30], except for the presence of hyphae of Candida sp. Candida was found in 27.7% of the specimens analyzed in this study, which is below the average of 50% found in other studies [30].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The most common histopathological features observed in our study were similar to those found in other studies [20,27,30], except for the presence of hyphae of Candida sp. Candida was found in 27.7% of the specimens analyzed in this study, which is below the average of 50% found in other studies [30].…”
Section: Discussionsupporting
confidence: 80%
“…Candida was found in 27.7% of the specimens analyzed in this study, which is below the average of 50% found in other studies [30]. Since the emergence of AIDS, the diagnosis of HIV-related oral lesions has been important to the diagnosis, monitoring, and staging of the syndrome.…”
Section: Discussionmentioning
confidence: 52%
“…CD4+ Tlymphocyte counts also help predict the development of opportunistic infections. [22][23] Reichart et al 24 found, in a study of 95 HIV-infected patients with clinical and histological evidence of OHL, the average CD4+ Tlymphocyte count was 149 cells/µL (range 10-470 cells/µL). Glick et al 25 found, in patients with OHL, the mean CD4+ T-lymphocyte count was 143.3 cells/µL.…”
Section: Discussionmentioning
confidence: 99%
“…Para ciertas formas de cáncer se ha detectado agregación en la familia por factores genéticos, como se observa en el cáncer de mama. Se ha determinado también de que algunos tipos de cáncer pueden vincularse con infecciones, ejemplo, virus de Hepatitis B y hepatoma, HTLV1 y linfoma de células T, cáncer de estomago y Helicobacter pylori, entre otros (2). También se conoce ampliamente que los pacientes infectados con VIH, durante la progresión de su enfermedad desarrollan un mayor riesgo de tumores, algunos de los cuales pueden estar relacionados a enfermedades que se adquieren sexualmente, como el virus de Papiloma.…”
Section: Importancia De La Detección Temprana De Cáncerunclassified